Mindfulness in the middle school classroom: Strategies to target social and emotional well-being of gifted students. (May 2018) - Doss, Kristy Kowalske; Bloom, Lisa
Instructors of a middle school gifted language arts class implemented a 30-day unit of study on mindfulness in order to help students learn techniques to alleviate stress, perfectionistic tendencies, and anxiety. Practicing mindfulness techniques, such as meditation, provides individuals with tools to understand the mind and body and encourages individuals to not dwell on past events or fixate on future events, appreciating the here and now and living in the moment. Some gifted students struggle with social and emotional issues such as perfectionism and anxiety, and these conditions can create a cycle of stress rooted in nervousness, agitation, and compulsive thoughts. Instructors explained the components of mindfulness, provided daily guided meditations, and encouraged students to apply the techniques in their everyday lives. Results varied for each student with some able to use the mindfulness exercises to combat problems, while others struggled with understanding the purpose or potential benefits of mindfulness.